FAKTOR-FAKTOR YANG MEMPENGARUHI PERILAKU AUDITOR DALAM PENGHENTIAN PREMATUR ATAS PROSEDUR AUDIT (Studi Empiris Pada Kantor Akuntan Publik di Medan, Pekanbaru, dan Batam) - Rahmadani, Syahira; Anisma, Yuneita; ', Rofika (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2017)
The research aims to analyze of factors that influencing auditor’s attitude in procedure of audit’s premature. Object of this research is public accountant which registered in Medan, Pekanbaru and Batam There are ninety six questionnaires were sent, but only sixty nine questionnaires are returned. That data are analyzed by linear regression method and SPSS program version 19. The variables were examined audit risk, locus of control, audit’s experience, time pressure, review and control from public accountant and self esteem in relation to ambition in procedure of audit’s premature. The results of this research showed audit risk has an effect in procedure of audit’s premature with 0,000 significance, locus of control has an effect in procedure of audit’s premature with 0,000 significance, audit’s experience has an effect in procedure of audit’s premature with 0,008 significance, time pressure has an effect in procedure of audit’s premature with 0,001 significance, review and control from public accountant has an effect in procedure of audit’s premature with 0,003 significance and self esteem in relation to ambition has an effect in procedure of audit’s premature with 0,009 significance. The results of this research also showed that coefficient R square is 51,7%. Each independent variables, gives the strong influence to dependent variable, it means independents variables could explain dependent variable well.Keywords : auditor, attitude, procedure, audit, premature.